Financial crises in Asia and Latin America : then and now - Kaminsky, Graciela L. ([s.n.] [S.l.], 1997)
Analyzes the extent to which past crises share common characteristics in Latin America, Asia, Europe and the Middle East. Also analyzes the regional differences in 76 currency crises and 26 banking crises in the period 1970 to 1995. Speculates why regional differences are narrowing.